Thrombin inhibitors: surgical considerations and pharmacology. (6th February 2013) - Breik, Omar; Tadros, Rami; Devitt, Peter
Abstract The new thrombin inhibitors have provided an exciting opportunity for effective thromboprophylaxis without some of the disadvantages of the current anticoagulants. These drugs are orally administered, have predictable pharmacokinetics and dose–response, do not require monitoring and have an acceptable safety profile when used appropriately. However, inappropriate prescribing of these drugs may lead to catastrophic consequences. Clinicians need to be aware of some of the drawbacks associated with the use of dabigatran and, in particular, its reduced clearance in the setting of renal failure and the lack of an effective reversing agent when bleeding does occur. In this review, the evidence for efficacy and safety of dabigatran is discussed. We also aim to provide practical clinical advice on the pre‐ and post‐operative management of the elective and emergency surgical patient on dabigatran and provide guidelines for the management of acute haemorrhage in the context of dabigatran therapy.